BUILD USING NETWORK LAN ROUTER CAN DO TO FULL CONTROL OF ACCESS SERVER - Sutarno Sutarno Sutarno (Majalah SIKOMTEK, 2004)
Local Area Network (LAN) is a network where companies hardware and software coupled toeach other can communicate in a particular work area using the data and has a high speed, sothat two or more networks can communicate with another network that is located very far inorder can perform a full access control from servers to workstations, his workstation ascontrolling management of a network by using routers.